Industry Loss Warranties: Contract Features, Pricing, and Central Demand Factors - Gatzert, Nadine; Schmeiser, Hato (The Journal of Risk Finance, 2012)
Purpose The purpose of this paper is to provide a detailed analysis of industry loss warranties (ILWs), an alternative risk transfer instrument which has become increasingly popular throughout the last few years. Design/methodology/approach The authors first point out key characteristics of ILWs important to investor and cedent, including transaction costs, moral hazard, basis risk, counterparty risk, industry loss index, and regulation. Next, the authors present and discuss the adequacy of actuarial and financial approaches for pricing ILWs, as well as the aspects of basis risk. Finally, drivers of demand and associated models frameworks from the purchaser's viewpoint are studied. Findings Financial pricing approaches for ILWs are highly sensitive to input parameters, which is important given the high volatility of the underlying loss index. In addition, the underlying assumption of replicability of the claims is not without problems. Due to their simple and standardized structure and the dependence on a transparent industry loss index, ILWs are low‐barrier products, which can also be offered by hedge funds. In principle, traditional reinsurance contracts are still preferred as a measure of risk transfer, especially since these are widely accepted for solvency capital reduction. However, the main important impact factor for the demand of ILWs from the perspective of market participants, i.e. large diversified reinsurers and hedge funds, is the lower price due to rather low transaction costs and less documentation effort. Hence, ILWs are attractive despite the introduction of basis risk and the still somewhat opaque regulatory environment. Research limitations/implications An important issue for future research is how reinsureds deal with the basis risk inherent in ILWs. Another central point is the development of a European industry loss index and the creation of an exchange platform to enable an even higher degree of standardization and a faster processing of transactions. Originality/value ILWs feature an industry loss index to be triggered, and, in some cases, a double‐trigger design that includes a company indemnity trigger. ILW contracts belong to the class of alternative risk transfer instruments that have become increasingly popular, especially in the retrocession reinsurance market. There has been no comprehensive analysis of these instruments in academic literature to date. Consequently, the authors believe that this paper provides a high degree of originality.
WiSo-Import:2015-03-26:945
Keywords: -